Determination of flood risk: A case study in the rainiest city of Turkey. (July 2017) - Şen, Olgay; Kahya, Ercan
Abstract: This paper combines hydrological and flood models for the purpose of estimating surface and peak flow rates from precipitation storm events occurred in basins of Rize province located in northern Turkey, receiving highest annual average precipitation height over 2300 mm. Two models: (i) Watershed Modeling System for predicting hydrographs and (ii) TuFlow comprised of hydrodynamic model of a one-dimensional river flow and a two-dimensional surface flow model for floodplain delineation were coupled to determine flood risks in the basins of Rize province. A 100-year flood peak discharges are computed based on the historical records and generated records in relation to climate change scenarios using grid-based approach. The influences of resolution of the mesh-size with the same DEM data on automated floodplain delineation are also another concern to investigate in this study. The results of this study could be used in quantitative flood risk assessments in the design of municipal infrastructures in the region. The results of this study showed that İyidere River flooded during the both present and future (tied with three climate change scenarios) conditions and seemed to need rehabilitation whereas Çağlayan and Tahiroğlu rivers flooded only in present condition. Our investigation also showed that coarse grid resolutions might cause overestimation in the floodplain and water depth. Highlights: Decreasing trends were observed to take place in the basins of Rize for peak discharges until 2069. Increasing trends appeared in all the basins of Rize at the end of the century, but it is still less than present condition at the rate of 35%. Iyidere River flooded during all scenarios and immediate action is recommended to rehabilitate it.